Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3390/ijerph7072853
|View full text |Cite
|
Sign up to set email alerts
|

Is Participation in After-School Physical Activity Associated with Increased Total Physical Activity? A Study of High School Pupils in the Czech Republic

Abstract: This study assessed the physical activity (PA) levels and its variability across days, months and seasons of two groups of high school pupils: those who did and those who did not participate in regular organized after-school physical activity (ASPA). Thirteen pupils wore pedometers continuously for one school-year, logged their step counts into record sheets and were then interviewed for information as regards their participation in any ASPA. Repeated measures analysis of variance showed that regardless of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Another reason of our outcomes can be that Polish adolescents have more opportunities to engage in after-school PA. After-school PA can be developed within the school setting and represents a critical window for promoting PA among youth, as well as for enhancing higher PA levels and reducing obesity risk (28). A study developed in the Czech Republic and focused on adolescents' PA demonstrated that exercising in after-school organized PA increases overall quantity of daily PA (29). Thus, it is clear that a wider offer of after-school activities could provide more favourable conditions for reaching higher PA levels.…”
Section: Physical Activity Levelsmentioning
confidence: 99%
“…Another reason of our outcomes can be that Polish adolescents have more opportunities to engage in after-school PA. After-school PA can be developed within the school setting and represents a critical window for promoting PA among youth, as well as for enhancing higher PA levels and reducing obesity risk (28). A study developed in the Czech Republic and focused on adolescents' PA demonstrated that exercising in after-school organized PA increases overall quantity of daily PA (29). Thus, it is clear that a wider offer of after-school activities could provide more favourable conditions for reaching higher PA levels.…”
Section: Physical Activity Levelsmentioning
confidence: 99%
“…In addition, the after-school period is considered a “critical interval” that defines the propensity of adolescents for physical activity [ 16 ]. The after-school period may represent significant opportunities for educators and researchers to modify exercise habits and enhance physical activity for adolescents reported by Pelclová et al [ 17 ]. In this study, we performed a cross-sectional investigation of environmental variables and health-related physical fitness, measuring five physical fitness indicators in Taiwanese adolescents aged 13–15 years.…”
Section: Introductionmentioning
confidence: 99%
“…Although PA of adolescents has attracted global debate regarding its characteristics (e.g. recommended levels, influence of organized PA on total PA, sedentary behaviour, age-related decline) [ 4 , 9 , 12 , 16 ], studies have usually focused only on assessing the levels of PA, without detailed information about the specific types of adolescents' PA [ 17 ]. The different types of PA and sedentary behaviour are important for understanding active and sedentary behaviours, and for effective design, planning, and support of interventions which aim to promote physically active lifestyles.…”
Section: Introductionmentioning
confidence: 99%